THE ART-ADVERTISING NEXUS: A BIBLIOMETRIC ANALYSIS OF VISUAL ARTS IN ADVERTISING. - John, Joshy; H., Divya; Bose, Jacob; Thomas, Sajan N (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Visual arts in advertising serve as a powerful medium to convey messages, evoke emotions, and enhance brand identity through visually compelling narratives. This bibliometric analysis, conducted using Biblioshiny and VOSviewer with data from the Scopus database, examines 82 documents published between 1960 and 2023, focusing on annual scientific production, relevant authors, and publication sources. Key findings reveal consistent growth in the field, with significant contributions from authors such as Huettl Verena and prominent sources like Developments in Marketing Science. A three-field plot highlights collaborations between authors, sources, and countries, while trend topics indicate a shift from traditional themes like creativity to emerging areas such as machine learning and social media. The thematic map categorizes research into motor, basic, niche, and emerging themes, emphasizing the dynamic and interdisciplinary nature of the field. Additionally, the co-occurrence of keywords reveals clusters linking foundational artistic principles with modern technological innovations, and the co-citation network underscores the foundational influence of key authors. This study identifies gaps such as limited global collaboration and underexplored areas, offering insights for researchers and practitioners to harness the transformative potential of visual arts in crafting impactful advertising strategies.